Efficacy of Surgery Combined with Autologous Bone Marrow Stromal Cell Transplantation for Treatment of Intracerebral Hemorrhage - Jianxin Zhu; Yilei Xiao; Zhongmin Li; Fabin Han; Taiwu Xiao; Zhiti Zhang; Fengyang Geng (Stem Cells International)
Bone marrow stromal cells (BMSCs) may differentiate into nerve cells under a certain condition; however, the clinical application for treating nervous system disease remains unclear. The aim is to assess the safety profile, feasibility, and effectiveness of surgery combined with autologous BMSCs transplantation for treating ICH. 206 ICH patients who had received surgical procedure were divided into transplantation (n=110) or control group (n=96). For transplantation group, BMSCs were injected into the perihemorrhage area in the base ganglia through an intracranial drainage tube 5.5 (3.01–6.89) days after surgery, followed by a second injection into the subarachnoid space through lumbar puncture 4 weeks later. Neurologic impairment and daily activities were assessed with National Institute Stroke Scale (NIHSS), Barthel index, and Rankin scale before transplantation and 6 months and 12 months after transplantation. Our results revealed that, compared with control group, NIHSS score and Rankin scale were both significantly decreased but Barthel index was increased in transplantation group after 6 months. Interestingly, no significant difference was observed between 12 months and 6 months. No transplantation-related adverse effects were investigated during follow-up assessments. Our findings suggest that surgery combined with autologous BMSCs transplantation is safe for treatment of ICH, providing short-term therapeutic benefits.